Living in a microplastic world: an analytical review of an insidious global contaminant (Engineering and Sustainability Journal, 2026)
This review aimed to consolidate and synthesize current knowledge on plastic pollution across its entire life cycle. It integrates data on production scale, plastic waste generation, mechanisms of microplastics (MPs) and nanoplastics (NPs) formation, their global environmental distribution, human exposure pathways, and toxicity mechanisms ranging from cellular effects to specific molecular pathways. The study is based on a comprehensive analysis of peer-reviewed scientific literature, including research on plastic production, environmental monitoring across aquatic, terrestrial, and atmospheric systems, human biomonitoring, toxicology (both in vitro and in vivo), and policy mitigation strategies. Data on production volumes, environmental concentrations, exposure estimates, and toxicological outcomes were compiled to create a cohesive narrative linking environmental science, human toxicology, and policy responses. The findings confirm the widespread presence of MPs, with contamination documented from Mount Everest to the Mariana Trench. Human bioaccumulation is evidenced by the detection of plastic particles in blood, placenta, and breast milk, demonstrating their ability to cross biological barriers. Primary exposure routes include ingestion (up to 5 grams per week) and inhalation, with contaminated intravenous fluids identified as an emerging direct pathway. Toxicological evidence shows that MPs induce oxidative stress and cellular dysfunction. Additives such as DCHP act as pregnane X receptor (PXR) agonists, linking exposure to lipid metabolism disruption and increased cardiovascular risk. Overall, MPs and NPs represent a growing threat to environmental and human health, highlighting the urgent need for coordinated global action and stronger regulatory frameworks.
Keywords: Plastic pollution; Microplastics (MPs) and nanoplastics (NPs); Human exposure and toxicity; Environmental distribution and bioaccumulation.